Penerapan Strategi Pembelajaran Berbasis Deep Dialogue Critical Thinking Dalam Meningkatkan Partisipasi Belajar Siswa Di MA Nu Nurul Ulum Jekulo Kudus - Anis, Moh. Badiul; Ustadi, Hadi; Wardani, Muhammad Agus (JPT : Jurnal Pendidikan Tematik, 2020)
The learning activities implemented by educators who teach Fiqh class XI subjects at MA NU Nurul Ulum Jekulo Kudus are in accordance with the theory of applying the deep dialogue critical thinking model, and developing in the process. Second: The effectiveness of the application of the deep dialogue critical thinking (DDCT) model in Fiqh class XI subjects at MA NU Nurul Ulum Jekulo Kudus using two assessment models, namely: a. Non-test: observation of students' attitudes in the learning process during dialogue. b. Test: memorization of oral, written (description, objective). Third: Supporting factors and obstacles to the implementation of the deep dialogue critical thinking (DDCT) model in Fiqh class XI subjects at MA NU Nurul Ulum Jekulo Kudus include: Supporting factors: 1) In terms of adequate infrastructure; 2) In terms of educators who are competent in the field of science; 3) In terms of other supporting subjects; 4) In terms of achievement of students or alumni as stimulation and motivation to continue to excel. While the inhibiting factor; 1) In terms of students who are lazy, passive and experience learning difficulties; 2) In terms of limited time allocation; 3) In terms of teaching staff.